2020
DOI: 10.4015/s1016237220500210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate Clinical Efficacy of Bioceramic Technology on Psychopathically Related Spasmodic Torticollis Using Motion Measurements, Computerized Analysis of Facial Emotions and Speech Signal Features

Abstract: Objective: Spasmodic torticollis is a debilitating neurological movement disorder associated with somatization, obsessive-compulsive, interpersonal sensitivity, depression, and anxiety. Usually, clinician had difficulty to precisely and quantitatively describe clinical outcomes using measurements of patients’ facial and neck movements. Methods: Motion speed changes and direction complexity, computerized facial emotion and assessment, measurement of speech signal features are the quantitative measurements of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…There were studies of patients with depression had found acoustic features, could be useful as biomarkers for evaluation of symptom severity and treatment efficacy for depression. In our study, it was indicated a significant decrease of fundamental frequency of the patient's SSF after the treatments of BR&PLB [12,16].…”
Section: Clinical Assessment Of Br With Instant Beneficial Effect On Patient With Psychopathically Related Spasmodic Torticollissupporting
confidence: 57%
See 2 more Smart Citations
“…There were studies of patients with depression had found acoustic features, could be useful as biomarkers for evaluation of symptom severity and treatment efficacy for depression. In our study, it was indicated a significant decrease of fundamental frequency of the patient's SSF after the treatments of BR&PLB [12,16].…”
Section: Clinical Assessment Of Br With Instant Beneficial Effect On Patient With Psychopathically Related Spasmodic Torticollissupporting
confidence: 57%
“…By selecting specific tempo frequencies of sound wave, device of BIOCERAMIC resonance produces vibration of specific meridian channels described by Traditional Chinese medicine (TCM), which brings to clinical benefits [7,8]. Our study was then begun from in vitro cell study of material science, and then go through different animal and human trials [6], There were under permissions with a series of IRB approvals, include Taipei Medical University & Hospital, Taipei Hospital and Taoyuan General Hospital [6][7][8][9][10][11][12][13][14]. In this review article, we present our experience base on clinical experimental results to explain and describe clinical efficacy BIOCERAMIC related technology that apply to mental and psychiatric related disorders [9][10][11][12][13][14].…”
Section: Bioceramic Related Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Our exploration of BR-related technology in mental and psychiatric disorders contributed to a comprehensive understanding of its versatility in mental health treatment. Studies on psychopathically related spasmodic torticollis [7], drug withdrawal symptoms [6], and extrasensory perception [9] provided quantitative frameworks for assessing clinical efficacy, collectively demonstrating BR's impact on neurological movement disorders and its potential applications in substance abuse treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation commenced with in vitro cell studies in material science and advanced through a series of animal and human trials. All these phases were conducted following approved Institutional Review Board (IRB) protocols from reputable institutions, including Taipei Medical University & Hospital, Taipei Hospital, and Taoyuan General Hospital [3,5,6,7,8,9,10,12,16,17 ].…”
Section: Methodsmentioning
confidence: 99%